2016
DOI: 10.1523/jneurosci.0262-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responses to Heartbeats in the Default Network Encode the Self in Spontaneous Thoughts

Abstract: The default network (DN) has been consistently associated with self-related cognition, but also to bodily state monitoring and autonomic regulation. We hypothesized that these two seemingly disparate functional roles of the DN are functionally coupled, in line with theories proposing that selfhood is grounded in the neural monitoring of internal organs, such as the heart. We measured with magnetoencephalograhy neural responses evoked by heartbeats while human participants freely mind-wandered. When interrupted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
182
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(205 citation statements)
references
References 66 publications
20
182
3
Order By: Relevance
“…First, we did not control for other cardio-respiratory parameters that might affect the HEP amplitude changes (Babo-Rebelo et al, 2016;Park, Correia, Ducorps, & Tallon-Baudry, 2014), and therefore, we are unable to account for their potential impact in our findings. First, we did not control for other cardio-respiratory parameters that might affect the HEP amplitude changes (Babo-Rebelo et al, 2016;Park, Correia, Ducorps, & Tallon-Baudry, 2014), and therefore, we are unable to account for their potential impact in our findings.…”
Section: Limitations and Conclusionmentioning
confidence: 98%
See 3 more Smart Citations
“…First, we did not control for other cardio-respiratory parameters that might affect the HEP amplitude changes (Babo-Rebelo et al, 2016;Park, Correia, Ducorps, & Tallon-Baudry, 2014), and therefore, we are unable to account for their potential impact in our findings. First, we did not control for other cardio-respiratory parameters that might affect the HEP amplitude changes (Babo-Rebelo et al, 2016;Park, Correia, Ducorps, & Tallon-Baudry, 2014), and therefore, we are unable to account for their potential impact in our findings.…”
Section: Limitations and Conclusionmentioning
confidence: 98%
“…Our study has a number of limitations that are worth noting. First, we did not control for other cardio-respiratory parameters that might affect the HEP amplitude changes (Babo-Rebelo et al, 2016;Park, Correia, Ducorps, & Tallon-Baudry, 2014), and therefore, we are unable to account for their potential impact in our findings. Similarly, the short intertrial interval of our experimental setup does not allow the computation of cardiac parameters, such as the interbeat interval and activity in the heart period power spectrum (Rajendra Acharya, Paul Joseph, Kannathal, Lim, & Suri, 2006).…”
Section: Limitations and Conclusionmentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, recent studies are starting to unveil relationships between oscillatory activity produced by different organ systems. For instance, Tallon-Baudry and collaborators have shown that ascending signals from the heart and gastrointestinal tract modulate brain dynamics and affect perception, emotion and cognition [10][11][12][13]. In particular, the EEG alpha rhythm was shown to be modulated by the phase of the gastric cycle [7].…”
Section: Introductionmentioning
confidence: 99%